Modulation of structural and functional traits in facultative halophyte Salvadora oleoides Decne. For adaptability under hyper-arid and saline environments. (June 2023) - Iqbal, Ummar; Hameed, Mansoor; Ahmad, Farooq; Ahmad, Muhammad Sajid Aqeel; Naz, Nargis; Ashraf, Muhammad; Kaleem, Muhammad
Abstract: Five differently adapted ecotypes were collected from (i) Jhang (JHG-mud flats near the Thal Desert margin), (ii) Rahim Yar Khan (RYK-sandy dunes of Cholistan Desert), (iii) Rajanpur (RJP-stony desert near the foothills), (iv) Lal Suhanra (LSR-hypersaline desert flat area), ( v) Khewra mine (KHM-salt affected and sandstone mountain) during the peak of flowering season to unravel the underlying mechanism involved in their ecological success. The ecotypes from desertified regions possessed large leaves, root and shoot K +, total soluble proteins, chlorophyll (chl a, b, tchl, chl a/b and tchl/caro) and carotenoids, and thick cortical region, enlarged pith and its cells area in stems, and leaf thickness in terms of midrib and lamina thickness, epidermal and mesophyll thickness and large sized vascular bundles in leaves. In comparison the ecotypes of salt affected areas surpassed in growth attributes, ionic contents especially root and shoot Na + and Ca 2+, osmoprotectants (total free amino acids and soluble sugars) and antioxidants (SOD, CAT and POD). From this finding, we concluded that S. oleoides evolved multiple tolerance mechanisms at the structural and functional level to ensure survival under hyper-arid and saline environments, and can be explored later at a genetic level to surrogate in sensitive species. Highlights: Ecological fitness of Salvadora oleoides is due to plasticity in structural and functional features. Functional traits were accumulation of ionic contents organic osmolyte and Antioxidants. Structural traits were formation of thick epidermis, intensive sclerification, enhanced stomatal index. Desert ecotypes showed development of xeromorphic traits in root, stem and leaves. It possessed the great proportion of total soluble protein, chlorophyll and root and shoot K + ion.